FDI(R) for satellites: howto deal with high availability and robustness in the space domain? - Olive, Xavier (Zielona Góra: Uniwersytet Zielonogórski)
The European leader for satellite systems and at the forefront of orbital infrastructures, Thales Alenia Space, is a joint venture between Thales (67%) and Finmeccanica (33%) and forms with Telespazio a Space Alliance. Thales Alenia Space is a worldwide reference in telecoms, radar and optical Earth observation, defence and security, navigation and science. It has 11 industrial sites in 4 European countries (France, Italy, Spain and Belgium) with over 7200 employees worldwide
Keywords: aerospace applications; discrete-event and hybrid systems; diagnosis; fault detection